2017
DOI: 10.1021/acs.inorgchem.7b02579
|View full text |Cite
|
Sign up to set email alerts
|

E–H (E = B, Si, C) Bond Activation by Tuning Structural and Electronic Properties of Phosphenium Cations

Abstract: In this work, strategic enhancement of electrophilicity of phosphenium cations for the purpose of small-molecule activation was described. Our synthetic methodology for generation of novel two-coordinate phosphorus(III)-based compounds [{CH(MeN)C}C·PR] ([2a], R = NPr; [2b], R = Ph) was based on the exceptional electron-donating properties of the carbodicarbene ligand (CDC). The effects of P-centered substituent exchange and increase in the overall positive charge on small substrate activation were comparativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In comparison, at elevated temperatures both NaBAr F and NaBAr Cl (BAr F = tetrakis(3,5-trifluoromethylphenyl)borate, BAr Cl = tetrakis(3,5-dichlorophenyl)borate) give simultaneous dehydrocoupling and P-H bond formation, in direct contrast to the behaviour of OTf, coupled with anion decomposition, either by hydrodehalogenation(BAr F ) or protodeboronation (BAr Cl ). On heating at 100 °C, the BAr F anion undergoes fluo-ride abstraction, leading to the formation of partially fluorinated phosphane centres and Et 3 SiF, confirmed by 11 B, 19 F and 29 Si NMR, but no change in the final 11 B NMR spectrum is observed on addition of excess pyridine, indicating an absence of free 3° boron species. In contrast, the BAr Cl system showed almost complete loss of signal intensity in the 11 B NMR, indicating protodeboronation and formation of BAr 3 species.…”
Section: Scheme 2: Reductive Coupling In the Presence Of Tmsotf Leadmentioning
confidence: 89%
See 1 more Smart Citation
“…In comparison, at elevated temperatures both NaBAr F and NaBAr Cl (BAr F = tetrakis(3,5-trifluoromethylphenyl)borate, BAr Cl = tetrakis(3,5-dichlorophenyl)borate) give simultaneous dehydrocoupling and P-H bond formation, in direct contrast to the behaviour of OTf, coupled with anion decomposition, either by hydrodehalogenation(BAr F ) or protodeboronation (BAr Cl ). On heating at 100 °C, the BAr F anion undergoes fluo-ride abstraction, leading to the formation of partially fluorinated phosphane centres and Et 3 SiF, confirmed by 11 B, 19 F and 29 Si NMR, but no change in the final 11 B NMR spectrum is observed on addition of excess pyridine, indicating an absence of free 3° boron species. In contrast, the BAr Cl system showed almost complete loss of signal intensity in the 11 B NMR, indicating protodeboronation and formation of BAr 3 species.…”
Section: Scheme 2: Reductive Coupling In the Presence Of Tmsotf Leadmentioning
confidence: 89%
“…We reasoned that unactivated hydrosilanes should nevertheless react with a sufficiently electrophilic P­(III) center; Vidović and Stephan recently reported analogous reaction of P­(III) dications with silanes. While ligand exchange reactions about donor-stabilized phosphenium cations have been studied in the past, , and they have been investigated as ligands in transition metal complexes, , comparatively little is known about their other reactivity, in part due to their perceived instability and high Lewis acidity .…”
Section: Introductionmentioning
confidence: 99%
“…Vidovićet al showed that the dicoordinate diamido-substituted phosphenium ion [( i Pr 2 N) 2 P] + (81) inserted into the B−H bond of aminoboranes to give four-coordinate boryl phosphonium salts 82 (Scheme 23). 86 The related dications 83 and 84, stabilized by the strongly donating carbodicarbene ligand, also cleaved the B−H bond of aminoboranes to give a mixture of hydridophosphenium (85) and hydrido boryl (86) products in the ratio of 1:23 for R = i Pr and 9:1 for R = Ph. These oxidative addition products were characterized by NMR spectroscopy and X-ray diffraction analysis.…”
Section: H−h Bond Activationmentioning
confidence: 99%
“…Recently the Vidović group showed that P III dications exhibit stoichiometric activation of C−F bonds at 100 °C, albeit with a limited scope of substrates (only α‐phenyl C−F bonds) . The same group also showed abstraction of hydrides from silanes and amine/pyridyl‐boranes under ambient conditions . Despite the above Lewis acidic behavior, applications of electrophilic P III compounds in catalysis have been limited to N‐heterocyclic phosphines (NHPs) and triaminophosphines…”
Section: Figurementioning
confidence: 99%